Post-Stroke Sleep-Disordered Breathing—Pathophysiology and Therapy Options - Stevens, David; Martins, Rodrigo Tomazini; Mukherjee, Sutapa; Vakulin, Andrew (Frontiers in Surgery, 2018)
Sleep disordered breathing, encompassing both obstructive and central sleep apnea, is prevalent in at least 50% of stroke patients. Small studies have shown vast improvements in post-stroke functional recovery outcomes after treatment of sleep disordered breathing by continuous positive airway pressure. However, compliance to this therapy is very poor in this complex patient group. There are alternative therapy options for sleep disordered breathing that may be more amenable for use in at least some post-stroke patients, including mandibular advancement, supine avoidance and oxygen therapy. However there are few studies which demonstrate efficacy and compliance with these alternative therapies currently. Furthermore novel sleep disordered breathing phenotyping approaches may help to provide important clinical information to direct therapy selection in individual patients. Prior to realising individualised therapy we need a better understanding of the pathophysiology of sleep disordered breathing in post-stroke patients, including the role of inherent phenotypic traits, as well as the contribution of stroke size and location. This review summarises the available literature on sleep disordered breathing pathophysiology and treatment in post-stroke patients, identifies gaps in the literature and sets out areas for further research.